2018
DOI: 10.1111/cob.12278
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac structure and function before and after bariatric surgery: a clinical overview

Abstract: Obesity, defined as a body mass index of ≥30 kg/m , is the most common chronic metabolic disease worldwide and its prevalence has been strongly increasing. Obesity has deleterious effects on cardiac function. The purpose of this review is to evaluate the effects of obesity and excessive weight loss due to bariatric surgery on cardiac function, structural changes and haemodynamic responses of both the left and right ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 79 publications
(376 reference statements)
1
9
0
Order By: Relevance
“…Evidence suggests that higher maternal BP in the first trimester of pregnancy is associated with a higher risk of hypertensive disorders later on 32 , therefore the lower BP found in postbariatric women may provide a plausible explanation for the reduced rates of hypertension and PE reported in this population 19,33 . In this study, CO increased with gestation in both groups, reflecting physiological pregnancy changes 10 ; however, in the postbariatric pregnant group, lower SV and HR resulted in lower CO, as observed in postbariatric individuals outside the context of pregnancy 29,34 .…”
Section: Discussionsupporting
confidence: 45%
“…Evidence suggests that higher maternal BP in the first trimester of pregnancy is associated with a higher risk of hypertensive disorders later on 32 , therefore the lower BP found in postbariatric women may provide a plausible explanation for the reduced rates of hypertension and PE reported in this population 19,33 . In this study, CO increased with gestation in both groups, reflecting physiological pregnancy changes 10 ; however, in the postbariatric pregnant group, lower SV and HR resulted in lower CO, as observed in postbariatric individuals outside the context of pregnancy 29,34 .…”
Section: Discussionsupporting
confidence: 45%
“…The independent associations of higher VAT and lower CRF with subclinical abnormalities in LV contractility highlight their potential role as modifiable targets for HF prevention [ 44 , 45 ]. Observational studies of individuals who have undergone bariatric surgery suggest that substantial weight loss can reverse pathological cardiac remodeling and reduce risk of incident HF[ 46 , 47 ]. More recently, findings from the Look AHEAD trial have demonstrated that greater loss of overall and central adiposity with lifestyle interventions is associated with lower risk of HF [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…With increments in adipose tissue and its vascular bed size in the case of overweight or obesity, as a compensatory mechanism, the sympathetic and renin-angiotensin-aldosterone (RAA) systems are activated to drive cardiovascular system overload for meeting the metabolic demands of extra adipose tissue. Long-standing overweight leads to cardiac volume- and pressure-overload, and higher cardiac output and blood pressure via activation of sympathetic and RAA systems, consequently causing myocardial fibrosis, ventricular maladaptive hypertrophy and enlargement with cardiac dysfunction, and increase of cardiovascular events and mortality 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Resultantly, hypoventilation, obstructive sleep apnea, hypoxia, hypercapnia and respiratory acidosis can then occur 22 . This chronic hypoxia and hypercapnia cause sympathetic-RAA system activation, vasoconstriction and hypertension with consequent overweight- or obesity-related cardiac geometric remodeling and dysfunction 20,22 . Additionally, accumulated adipose tissue can secrete RAA components, which can activate sympathetic and RAA systems, leading to adverse cardiac dysfunction 23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation